The Phenomenon of Change from Sellers Using Candy in Sharia Business Ethics - Fikriyah, Khusnul; Alam, Wira Yudha (Nursyam Center, 2024)
This article aims to discuss in depth the phenomenon of replacing change with candy that is widely practised by business actors in the buying and selling process from the perspective of sharia business ethics. Basically, buying and selling in Islam is a permissible activity. However, in the process there are interesting activities to be studied from an Islamic perspective, one of which is this phenomenon. This type of research is descriptive qualitative. While literature study is used as a data collection technique. The results of this study show that sharia business ethics sees that in th relations between humans (muamalah), all things can be done, unless there is clear evidence that prohibits it. In this case, when business actors do not pay full return, there are buyer rights that are not given by business actors. If the buyer is not happy with the return, then even very small change becomes bastard (haram) because it was taken in a bad way (batil). Not giving the full change, or the change is replaced with candy by the business is also not in accordance with the principles of Islamic economic ethics, which consist of Tawhid, balance, free will, and responsibility